2021
DOI: 10.3390/s21248227
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Hybrid Deep Learning Model for Human Activity Recognition Based on Transitional Activities

Abstract: In recent years, a plethora of algorithms have been devised for efficient human activity recognition. Most of these algorithms consider basic human activities and neglect postural transitions because of their subsidiary occurrence and short duration. However, postural transitions assume a significant part in the enforcement of an activity recognition framework and cannot be neglected. This work proposes a hybrid multi-model activity recognition approach that employs basic and transition activities by utilizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Several studies have proposed effective systems for recognizing transition states in human action. For instance, real-time ML-based methods have been employed for automatic segmentation and recognition of continuous human daily action by integrating change point detection algorithms with smart home action recognition [37], [38]. Among them, an online change point detection strategy was introduced [36] that segmented continuous multivariate timeseries smartphone sensor data and applied it to a transitionaware action recognition framework based on the hypothesis and verification principle.…”
Section: Transition-aware Action Recognitionsmentioning
confidence: 99%
“…Several studies have proposed effective systems for recognizing transition states in human action. For instance, real-time ML-based methods have been employed for automatic segmentation and recognition of continuous human daily action by integrating change point detection algorithms with smart home action recognition [37], [38]. Among them, an online change point detection strategy was introduced [36] that segmented continuous multivariate timeseries smartphone sensor data and applied it to a transitionaware action recognition framework based on the hypothesis and verification principle.…”
Section: Transition-aware Action Recognitionsmentioning
confidence: 99%
“…The results of hybrid deep learning model consists of CNN, LSTM ,and BiLSTM in [56] exhibited the accuracies of 98.38% on the Human Activity dataset with transition and basic activities and 96.11% on the HAPT dataset. In [57] article, a hybrid deep CNN-LSTM with Self-Attention model using Wearable Sensors for the classification of daily activities and get accuracy 93.11% and 98.76% for UCI-HAR and MHEALTH datasets.…”
Section: Hybrid Deep Learning-based Model Harmentioning
confidence: 99%
“…Previous research on human activity recognition (HAR) using artificial intelligence (AI) and machine learning (ML) has focused primarily on accurately predicting classes of known, human-labeled activities for each observation of network device telemetry data for specific human subjects. These models have typically been trained on labeled activities from specific subjects, and as such generally have subject dependency recognition constraints and their accuracy in identifying activities depends in large part on the feature selection process (1), (10), and (11). These studies have indicated that there are potentially several machine learning and deep learning algorithms that can be applied with varying degrees of success to achieve some degree of reliability for multinomial HAR classification accuracies.…”
Section: Statement Of the Problemmentioning
confidence: 99%